The structure of discussion: a discourse analytical approach to the identification of structure in the text type 'discussion' - Harrison, Julia (2002)
This study is concerned with the structural analysis of a corpus of discussive data. The data, mainly taken from CANCODE, the Cambridge and Nottingham Corpus of Discourse in English, was taken from a range of situational contexts, along a cline of formality from informal ï¿½chatï¿½ to public broadcast material. The data was analysed using a version of the Sinclair and Coulthard (1975) model of discourse, which was adapted to deal with spoken discussion, and the resultant analytical framework was described in detail.